The Application of Zonisamide to Patients Suffering from Dementia with Lewy Bodies: Emerging Clinical Data - Tousi B; Leverenz JB (Dove Medical Press, 2021)
Babak Tousi,1,2 James B Leverenz2 1Cleveland Clinic Lerner College of Medicine of Case Western Reserve University, Cleveland, OH, USA; 2Lou Ruvo Center for Brain Health, Cleveland Clinic, Cleveland, OH, USACorrespondence: Babak TousiLou Ruvo Center for Brain Health, U-10, Cleveland Clinic, 9500 Euclid Ave, Cleveland, OH, 44195, USATel +1 216 237 6400Email batous@ccf.orgAbstract: Zonisamide is an anti-epileptic medication with multiple mechanisms of action and a favorable safety profile. Zonisamide may interact with Lewy body dementia pathophysiology through a mechanism unrelated to its original indication. Zonisamide has shown efficacy as adjunct therapy for the management of motor symptoms in patients with Parkinson’s disease (PD). Given that dementia with Lewy bodies (DLB) and PD are considered subtypes of a Lewy body disease spectrum, zonisamide was investigated for the treatment of parkinsonism in DLB. Phase II and phase III clinical trials were conducted in patients with DLB in Japan. In both studies, participants were randomized to receive 12 weeks of zonisamide 25 or 50 mg/day or placebo. Zonisamide significantly improved the Unified Parkinson’s Disease Rating Scale Part III (UPDRS-III) without affecting the Mini-Mental State Examination (MMSE) or Neuropsychiatry Inventory-10 (NPI-10) scores at week 12. In 2018, zonisamide received Japanese regulatory approval for the additional indication of parkinsonism in DLB. This review discusses the emerging clinical data on zonisamide in the field of DLB.Keywords: dementia with Lewy bodies, zonisamide, clinical trial, parkinsonism